Higher Order of Convergence with Multivalued Contraction Mappings - Jia-Bao Liu; Asma Rashid Butt; Shahzad Nadeem; Shahbaz Ali; Muhammad Shoaib (Journal of Mathematics)
In this paper, we establish some theorems of fixed point on multivalued mappings satisfying contraction mapping by using gauge function. Furthermore, we use Q- and R-order of convergence. Our main results extend many previous existing results in the literature. Consequently, to substantiate the validity of proposed method, we give its application in integral inclusion.